ANALISIS STRUKTURAL PADA NOVEL “CRYING WINTER (MUSIM DINGIN YANG MEMILUKAN)” KARYA MELL SHALILA - Angel Oktoria Manise Marbun; Ester Mariam Silaban; Natasya Rumondang Sidabutar; Fitriani Lubis (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The purpose of this study is to describe the structure and interrelationships between elements in the novel CRYING WINTER by Mell Shalila. The research method used is qualitative research with a structural approach. Sources of data were obtained using secondary data which type is used to support the primary information that has been obtained, namely from library materials, literature, previous research, books, and so on. The data collected is in the form of text related to the building elements of the novel. The data source for this research is the novel CRYING WINTER by Mell Shalila. Data collection techniques using library techniques. Data analysis techniques, namely making a synopsis, describing the elements of the building structure contained in the novel CRYING WINTER by Mell Shalila, analyzing the relationship between building elements contained in the novel CRYING WINTER by Mell Shalila , and draw conclusions. The results of the research are in the form of intrinsic elements contained in the novel, namely theme, plot, setting, characters, characterizations, point of view, story style, and message. Where all these elements are interrelated and form a complete meaning.